Lactic acid fermentation from Jatropha curcas L. press cake and raw cassava starch using Rhizopus oryzae NRRL-395 - Perdon, Liza Rowena DLC.; Elegado, Francisco B.; Migo, Veronica P.; Movillon, Jovita L.; Demafelis, Rex B. (2011)
The utilization of Jatropha curcas L. for biodiesel production, produces a significant amount of press cake as a by-product. Toxic compounds render the cake unsustainable for animal feed. Thus other uses such as substrate for fermentation should be explored. Its use for lactic acid production was tried in this study. Dilute-aid hydrolysis of Jatropha press cake substrate was initially optimized, specifically pH conditions and duration of autoclaving. The highest value of reducing sugar recorded was 86.6 g/L obtained by hydrolizing the samples at pH 1.0 for 30 minutes. Upon fermentation with Rhizopus oryzae NRRL-395, starch supplemented hydrolyzed Jatropha press cake produced 3.67 g/L lactic acid in one day at pH 5.0. On the other hand, unhydrolyzed press cake took four days to ferment, but attained the highest value of 11.93 g/L lactic acid. Hydrolyzed samples could have produced sugars that are not utilizable by Rhizopus oryzae. The use of Jatropha press cake as protein supplement for the fermentation of raw cassava starch into lactic acid was feasible. This would probably provide a good alternative to reduce the fermentation costs due to chemical supplements. Further optimization is still needed for it to be suitable for large scale production.
Keywords: Lactic acid; Fermentation; Jathropa curcas; Cassava flour